Mathematics Teaching via Counting - De Veyra, Nimfa R (NeuroQuantology, 2022)
The performance of the students in their learning of mathematics is impacted by some teachers' incompetence, which directly impacts their function as learning facilitators. A passionate and approachable teacher, together with the methodology they apply or use, can help grow and correct many of the learner's inadequacies. Learning mathematics becomes enjoyable and natural when teachers model positive attitudes about the subject for their students. the idea that studying mathematics requires adults to solve relevant, real-world problems It is also believed that developing an interest in and favorable attitudes toward mathematics comes from learning to solve issues using mathematical information, such as the way outlined above..